Theorising play in the early years - Fleer, Marilyn; Fleer, Marilyn; Goncu, Artin (Cambridge ; Port Melbourne, Victoria : Cambridge University Press, 2014)
'A theoretical and empirical exploration of the concept of pedagogy and play in early childhood education ... provides an in-depth examination of classical and contemporary theories of play, with a focus on post-developmental perspectives and Vygotskian theory.'--Provided by publisher.
Marilyn Fleer is affiliated with Monash University, Victoria.
'Designed as a companion to the textbook Play in the Early Years, but also useful on its own.'--Page 4 of cover.
Includes bibliographical references and index.
Keywords: Early childhood education -- Activity programs; Play -- Study and teaching (Early childhood) -- Activity programs; Play; Education -- Philosophy; Play assessment (Child psychology).; Play -- Psychological aspects